Broadband High‐Power GaN SPDT Switch Using Stacked‐Shunt Fets and Resonance Inductors. Issue 9 (27th June 2013) - Hettak, Khelifa; Ross, Tyler N.; Cormier, Gabriel; Wight, Jim S.
ABSTRACT This article presents a new GaN HEMT‐based high‐power single‐pole double‐throw (SPDT) switch operating over the X‐band frequencies. The GaN SPDT MMIC switch is presented, having good return loss (better than 16.8 dB) and insertion loss (1.4 dB) measured across X‐band. It also has a very high power–handling capability, with a measured 1 dB compression point of 38 dBm. The techniques and design principles leading to this level of performance are discussed. Circuit performance is confirmed by experimental and simulation results, which are in good agreement up to 20 GHz. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2093–2095, 2013